Polymethylmethacrylate Collagen Gel–Injectable Dermal Filler for Full Face Atrophic Acne Scar Correction. Issue 12 (December 2019) - Joseph, John H.; Shamban, Ava; Eaton, Laura; Lehman, Alayne; Cohen, Steven; Spencer, James; Bruce, Suzanne; Grimes, Pearl; Tedaldi, Ruth; Callender, Valerie; Werschler, Phillip
Abstract : BACKGROUND/OBJECTIVES: This trial evaluated the effectiveness and safety of Bellafill for full-face acne scar treatment. PATIENTS AND METHODS: In this open-label, nonrandomized, multicenter pilot study investigating the use of polymethylmethacrylate for full-face atrophic acne scar correction, 42 adult subjects with a mean age of 43 years were treated and assessed for safety and effectiveness at Months 4 and 7. There were no hypersensitivity reactions to pretreatment skin testing or during scar treatments. RESULTS: At 4 and 7 months after initial treatment, 92% and 95% of subjects, respectively, were responders with ≥1-point improvement on the 5-point Acne Scar Assessment Scale. Subjects reported very high levels of improvement on the Global Aesthetic Improvement Scale (GAIS), with 95% of subjects reporting "improved or better" at 4 months and 90% at 7 months. The outcome of the physician GAIS was also high with 92% of patients classified as "improved or better" at 4 months and 97% at 7 months. There were only 2 device-related adverse events, both mild events related to Bellafill skin test (bruising, ecchymosis). There were no serious adverse events in response to the treatment product in this short-term follow-up study. CONCLUSION: Polymethylmethacrylate is effective for treating full-face acne scarring. Clinicaltrials.gov #NCT02642627.